Legal Aspects in Al Murabahah Financing Contract in Sharia Banking: Study at PT. Bank Syariah Indonesia Tbk Kedaton Branch, Bandar Lampung - Dwi Rimadona (Penerbit Goodwood, 2023)
Purpose: This study aims to obtain a complete, clear, detailed, and systematic description of the legal aspects of a murabahah contract Methodology: The research used is normative-empirical legal research by examining all sources of legislation and direct descriptions in the field, with a conceptual approach. Results: Murabahah contract is a sale and purchase contract of an item where the seller mentions the selling price and profit level, where the selling price is approved by the buyer. The characteristic is that the seller must tell the price of the product and determine a level of profit. The legal aspects in the murabahah contract include legal subjects, legal objects, legal events, and legal relationships.